Prevalence of Orthodontic Malocclusion and Evaluation Criteria in 7 Geographic Regions of Turkey - Burcu Nur; Duygu İlhan; Erdoğan Fişekçioğlu; İnci Oktay; Tülin Arun (Galenos Yayinevi, 2013)
Objective:The aim of this study was to identify the prevalence of malocclusion and orthodontic evaluation criteria in Turkey and determine differences among the 7 regions.Materials and Method:In our research, extra- and intraoral examination of 1023 randomly selected persons from rural and central parts of different regions (500 female subjects and 523 male subjects; mean age = 13.10 ± 3.11) were performed. To analyze the data, descriptive statistical methods (mean value, prevalence ratio, standard deviation) were carried out. The significance of regional differences of the evaluation criteria and gender distributions were assessed by means of a χ2 test.Results:Comparison of the classification of malocclusion, crossbite, chin deviation asymmetry, smile line, cleft lip and palate, and profile among the regions showed significant differences (p < 0.05). Class I, II, and III malocclusion was most frequently noted in the Marmara, Aegean, and Central Anatolia regions, respectively. Crossbite was found more frequently on the posterior side (27,4%). Of those with a high smile line, 29.1% were found in the Aegean region. Persons with cleft lip and palate were more frequently identified in the Black Sea, Southeastern Anatolia, and Aegean regions. Midline diastema (6.5%) and openbite (2.9%) in the study group showed no differences between gender and the 7 regions (p > 0.05).Conclusion:Malocclusion and all orthodontic evaluation criteria except midline diastema (p < 0.05) and openbite (p < 0.01) demonstrated statistically significant differences among the 7 regions of Turkey. As a result, we suggest that the distribution of orthodontic anomalies in the different geographic areas should be examined separately to give a more accurate picture of the actual occurrence rate and, therefore, contribute to the development of targeted health policies.